Improved clinical outcomes with a modified warming protocol in donor oocyte cycles - Chun-I Lee; Hsiu-Hui Chen; Shu-Hui Lin; Chun-Chia Huang; Pin-Yao Lin; Tsung-Hsien Lee; Ming-Jer Chen; Maw-Sheng Lee; Chien-Hong Chen (Journal of Ovarian Research)
Abstract Background Recent studies have attempted to improve laboratory efficiency while preserving clinical outcomes by shortening the time to warm cryopreserved embryos, though it is still unclear for oocytes. This study thus aimed to evaluate the effects of a modified warming protocol (MWP) on embryonic development and pregnancy outcomes of vitrified donor oocytes. Methods The data of this retrospective cohort study were collected from women who underwent donor cycles (fresh or vitrified oocytes) at Lee Women’s Hospital, Taiwan, from January 2019 to August 2024. The sample included 13,103 donor oocytes, divided into three groups: conventional warming protocol (CWP) group (n = 8506), MWP group (n = 980), and fresh group (n = 3617). Results Survival rates after oocyte warming were similar between the CWP and MWP groups (93.7% vs. 93.9%, P > 0.05). Oocyte degeneration rates post-intracytoplasmic sperm injection (ICSI) were similar for vitrified-warmed and fresh oocytes (2.7–3.4% vs. 2.8%). Normal fertilization was lower for vitrified-warmed oocytes (79.5–79.6% vs. 83.0%, P < 0.05), while abnormal fertilization was higher (9.1–10.1% vs. 3.3%). Blastocyst formation and usable blastocyst formation were lower in the CWP group (57.5% and 35.4%) compared to MWP (77.3% and 51.4%) and fresh groups (69.2% and 48.5%). Ongoing pregnancy/live birth was higher in the MWP group than in the CWP group (66.7% vs. 50.4%, P < 0.05). Multivariate analysis showed a positive association between MWP and usable blastocyst formation (adjusted incidence rate ratio = 1.423, 95% CI = 1.268 to 1.597, P < 0.001), as well as ongoing pregnancy/live birth (adjusted odds ratio = 1.899, 95% CI = 1.002 to 3.6, P < 0.05). Conclusions This study suggests that the MWP enhances the blastocyst formation potential and pregnancy outcomes of vitrified-warmed oocytes, making it similar to that of fresh oocytes. Thus, the MWP may replace the CWP as the standard protocol for optimizing donor cycle outcomes. Clinical trial number Not applicable.